Numerical study of shear thickening fluid with discrete particles embedded in a base fluid - W Zhu; Y Kwon; J Didoszak (International Journal of Multiphysics, 2016)
The Shear Thickening Fluid (STF) is a dilatant material, which displays non-Newtonian characteristics in its unique ability to transit from a low viscosity fluid to a high viscosity fluid. The research performed investigates the STF behavior by modeling and simulation of the interaction between the base flow and embedded rigid particles when subjected to shear stress. The model considered the Lagrangian description of the rigid particles and the Eulerian description of fluid flow. The numerical analysis investigated key parameters such as applied flow acceleration, particle distribution and arrangement, volume concentration of particles, particle size, shape and their behavior in a Newtonian and non-Newtonian fluid base. The fluid-particle interaction model showed that the arrangement, size, shape and volume concentration of the particles had a significant effect on the behavior of the STF. Although non-conclusive, the addition of particles in non-Newtonian fluids showed a promising trend of improved shear thickening effects at high shear strain rates.